2011
DOI: 10.2987/10-6097.1
|View full text |Cite
|
Sign up to set email alerts
|

Semi–Field Evaluation of Several Novel Alkenol Analogs of 1-octen-3-ol As Attractants to Adult Aedes albopictus and Culex quinquefasciatus

Abstract: The compound 1-octen-3-ol is a known attractant of some mosquito species, which has led to the hypothesis that olfactory stimulation by this alkenol may be associated with the following structural elements: a terminal site of unsaturation or high electron density; a structural capability for hydrogen bonding, e.g., -OH, -NH2, NHR, NR2, etc.; a saturated hydrocarbon chain of a certain minimum length; and a certain relative distance between the region of high electron density and the alcohol (or other hydrogen-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…sitiens at all concentrations. This finding is similar to previous research by Cilek et al [23] that reported that octanol attracted Ae. albopictus better than Cx.…”
Section: Discussionsupporting
confidence: 93%
“…sitiens at all concentrations. This finding is similar to previous research by Cilek et al [23] that reported that octanol attracted Ae. albopictus better than Cx.…”
Section: Discussionsupporting
confidence: 93%
“…Further, not all mosquito species respond equally to octenol [5], and whether different groups of alcohols would increase attractant activity for such species has been discussed [10]. However, a clear structure-activity relationship has not been demonstrated [14]. …”
Section: Discussionmentioning
confidence: 99%
“…This route would, beside the formation of 2-hydroxy-2-methoxyacetaldehyde, be responsible for the primary generation of PAN through the further reaction of the acetyl radical with O 2 /NO 2 . In addition, PAN is known to be formed due to the oxidation of methyl glyoxal (Fischer et al, 2014). The reaction of OH radicals with methyl glyoxal occurs exclusively by abstraction of the aldehydic H atom to form CH 3 C(O)CO radicals, which have a very short lifetime, dissociating to form CH 3 CO + CO (Green et al, 1990).…”
Section: Reaction Product Distribution and Mechanismmentioning
confidence: 99%
“…R. G. Gibilisco et al: Atmospheric fate of two relevant unsaturated ketoethers α, β-unsaturated ketoethers are compounds with high structural complexity found in the atmosphere. They were detected as reaction products of the atmospheric degradation of furans and unsaturated ethers, compounds which received substantial interest in the last decade, since they are considered promising alternative fuels (Cilek et al, 2011;Li et al, 2018;Villanueva et al, 2009;Zhou et al, 2006). UKEs are also produced during combustion and more specifically in biomass burning (Hatch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%